MOTHERHOOD ANALYSIS IN THE MAIN FEMALE CHARACTER OF THE NOVEL "LEBIH SENYAP DARI BISIKAN" BY ANDINA DWIFATMA - Alfia Amilia Fitri; Widyashanti Kunthara Anindita (Acceleration: Multidisciplinary Research Journal, 2023)
One example of a novel with the theme of feminism is "Lebih Senyap Dari Bisikan (More Silent Than a Whisper)" by Andina Dwifatma. This study examines how the concept of motherhood and Amara's image as a mother are depicted from the physical, psychological, and social aspects in the novel "Lebih Senyap Dari Bisikan" by Andina Dwifatma. There are 9 research data in the form of quotations which include 26 sentences consisting of 8 sentences describing the concept of "motherhood", and 18 sentences describing the image of Amara's character as a mother from physical, psychological, and social aspects. The data analysis technique used is descriptive qualitative accompanied by the analysis of Culler's feminist literary criticism, namely "Reading as a Woman". The results showed that many sentences depicted the concept of motherhood and that the main female character, Amara, was imaged more in the psychological and social aspects during childcare than during her pregnancy, and experienced more problems related to psychological and social relationships with people around her. In addition, Amara is also portrayed as a mother in the physical aspect but with low intensity in caring for the child she gave birth to.